Advanced Data Mining and Applications 7th International Conference, ADMA 2011, Beijing, China, December 17-19, 2011, Proceedings, Part I - Tang, Jie.; King, Irwin; Chen, Ling.; Wang, Jianyong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNAI 7120 and LNAI 7121 constitutes the refereed proceedings of the 7th International Conference on Advanced Data Mining and Applications, ADMA 2011, held in Beijing, China, in December 2011. The 35 revised full papers and 29 short papers presented together with 3 keynote speeches were carefully reviewed and selected from 191 submissions. The papers cover a wide range of topics presenting original research findings in data mining, spanning applications, algorithms, software and systems, and applied disciplines.
Keywords: Computer science; Computer software; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity